KOLABORASI MULTIAKTOR DALAM PENGENTASAN WILAYAH BLANKSPOT DI KABUPATEN SOLOK SELATAN - annisa aulia putri; Syamsu Rizaldi; Firdaus Firman (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
Solok Selatan Regency is one of the areas that once had the status of a 3T area in West Sumatra Province, where there are still many blindspot areas. To be able to level the telecommunication network, the Government of Solok Selatan Regency cooperates with various parties, including through Nagari-Owned Enterprises, PT Indonesia Comnet Plus or Icon+, as well as the Nagari Government and community groups in the Nagari. From several previous studies, it appears that collaboration makes a major contribution to the development of a region. Departing from these previous research studies, the researcher is interested in studying further related to multi-actor collaboration in alleviating blindspot areas in Solok Selatan Regency. This research is a type of qualitative research with descriptive analysis. The data source is the actors involved in alleviating blind spot areas in Solok Selatan Regency. Data collection through interviews and documentation as well as observation. The results showed that the actors involved in alleviating blankspot areas in Solok Selatan Regency were the Government of South Solok Regency (Diskominfo), PT Indonesia Comnet Plus (Icon+), Nagari Government and BUMNag. There are many benefits to be gained if this collaboration can run optimally in all villages which are included in blind spot areas. In addition, the distribution of telecommunication networks in South Solok Regency can also have a positive impact on increasing the quality of public services in South Solok Regency.